Search for lepton-flavour-violating decays of Higgs-like bosons; The European Physical Journal C; Vol. 78, iss. 12 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Aidala C. A. Christine; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen